2013
DOI: 10.4174/jkss.2013.85.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of neoadjuvant adriamycin and docetaxel versus adriamycin, cyclophosphamide followed by paclitaxel in patients with operable breast cancer

Abstract: PurposeNeoadjuvant chemotherapy is the standard treatment for patients with locally advanced breast cancer and is increasingly considered for patients with operable disease. Recently, as many clinical trials have demonstrated favorable outcomes of anthracycline-taxane based regimen, this approach has been widely used in the neoadjuvant setting.MethodsWe compared women who received adriamycine and docetaxel (AD) with adriamycin, cyclophosphamide followed by paclitaxel (AC-T) as neoadjuvant chemotherapy. The AD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
0
8
0
2
Order By: Relevance
“…Paclitaxel (PTX) is a kind of natural antitumour drug from the bark of the yew tree, which has unique pharmacological effects and used as the first‐line and second‐line chemotherapy drug for breast cancer, ovarian cancer and non‐small cell lung cancer, as well as it can be used in the treatment of head and neck cancer, oesophageal cancer . Although paclitaxel is sensitive and effective for breast cancer, it has many toxic reactions, such as allergic reaction, myelosuppression and neurotoxicity .…”
Section: Introductionmentioning
confidence: 99%
“…Paclitaxel (PTX) is a kind of natural antitumour drug from the bark of the yew tree, which has unique pharmacological effects and used as the first‐line and second‐line chemotherapy drug for breast cancer, ovarian cancer and non‐small cell lung cancer, as well as it can be used in the treatment of head and neck cancer, oesophageal cancer . Although paclitaxel is sensitive and effective for breast cancer, it has many toxic reactions, such as allergic reaction, myelosuppression and neurotoxicity .…”
Section: Introductionmentioning
confidence: 99%
“…After removing the studies with irrelevant topic or in non-English language, 171 articles were potentially eligible. After another round of screening, four eligible studies with 2,302 early-stage breast cancer patients were finally included in the quantitative synthesis (12)(13)(14)(15). The assessment of Cochrane risk of bias was illustrated in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…They found that after a median follow-up of 35.5 months, the DFS of the two arms was similar (log-rank, P=0.719) and that the incidence of treatment-related toxicity did not differ significantly ( 15 ). Moreover, Hong et al ( 16 ) reported that there was no significant difference in treatment response between AD (50/75 mg/m 2 adriamycin/docetaxel at a 3-week interval for 4 cycles each) and AC-T (50/500 mg/m 2 adriamycin/cyclophosphamide followed by 175 mg/m 2 paclitaxel at a 3-week interval for 4 cycles each) as NAC in patients with operable breast cancer ( 16 ). Both of the aforementioned studies showed no inferiority in the short-term therapeutic effects of concurrent treatment, which was consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…The concurrent administration of anthracyclines and taxanes hyas been reported to have more severe hematological toxicities compared to sequential and anthracycline-based regimens ( 6 , 16 ). The primary prophylactic use of G-CSF based on National Comprehensive Cancer Network guidelines for a higher risk of febrile neutropenia (FN) was also recommended ( 6 , 17 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation